2016
DOI: 10.1080/14786419.2016.1219862
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease

Abstract: In this study, a series of novel ferulic and caffeic acid dimers was designed and synthesised, and their multifunctional properties against Alzheimer's disease (AD) were evaluated. Results showed that our multifunctional strategy was great supported by enhancing the inhibition of Aβ self-induced aggregation. Moreover, 7b also had potent protective effects against glutamate-induced cell death without significant cell toxicity in mouse hippocampal neuronal HT22 cells and 10c effectively scavenged diphenylpicrylh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Additionally, mice treatment with caffeic acid and ferulic acid attenuated the effects of iron overload on the rat serum biochemical parameters [42][43][44]. Strikingly, ferulic and caffeic acid supplementation have shown positive effects toward prevention of multiple aspects of the metabolic syndrome and liver steatosis in an obese mouse model [45], multifunctional properties against Alzheimer's disease (AD) [46], and the anti-cancer activity has been demonstrated by their ability to mediate Cell Protection by Oxidative Stress Mitigation Using Substances with Bioactive Properties DOI: http://dx.doi.org/10.5772/intechopen.1004522 cytotoxicity toward human breast cancer cell lines that in the future could be profitably applied for chemopreventive and/or chemotherapeutic purposes [47].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Additionally, mice treatment with caffeic acid and ferulic acid attenuated the effects of iron overload on the rat serum biochemical parameters [42][43][44]. Strikingly, ferulic and caffeic acid supplementation have shown positive effects toward prevention of multiple aspects of the metabolic syndrome and liver steatosis in an obese mouse model [45], multifunctional properties against Alzheimer's disease (AD) [46], and the anti-cancer activity has been demonstrated by their ability to mediate Cell Protection by Oxidative Stress Mitigation Using Substances with Bioactive Properties DOI: http://dx.doi.org/10.5772/intechopen.1004522 cytotoxicity toward human breast cancer cell lines that in the future could be profitably applied for chemopreventive and/or chemotherapeutic purposes [47].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…In addition to direct application, scholars synthesized a series of dimers from caffeic acid and ferulic acid, and found that they could effectively remove DPPH and strongly inhibit the self-induced aggregation of Aβ (1-42) (He et al, 2017). In contrast, the prepared crystalline caffeic acid also showed neuroprotective effect as well as biological effects on AD on R28 cell line with the addition amount less than 6 μg/mL (Khan et al, 2016).…”
Section: Caffeic Acidmentioning
confidence: 99%
“…Moreover, compound 50 (Fig. 25 ) also showed potent protective effects against glutamate-induced cell death without significant cell toxicity in mouse hippocampal neuronal HT22 cells, whereas 51 effectively scavenged diphenyl-1-picrylhydrazyl (DPPH) free radicals assay [ 147 ].…”
Section: Curcumin Derivatives and Analoguesmentioning
confidence: 99%